2014
DOI: 10.1542/peds.2013-1707
|View full text |Cite
|
Sign up to set email alerts
|

Income Inequality and Child Maltreatment in the United States

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Income inequality is positively associated with several adverse child health and well-being outcomes. There is no existing research investigating the relationship between income inequality and child maltreatment rates. WHAT THIS STUDY ADDS:This study is the first to demonstrate that increases in income inequality are associated with increases in child maltreatment rates at the county level. abstract OBJECTIVE: To examine the relation between county-level income inequality and rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
101
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(115 citation statements)
references
References 37 publications
9
101
1
4
Order By: Relevance
“…An analysis of adolescent health in 34 mostly high-income countries found that national income inequality related to higher body mass indices, less physical activity, and more self-rated mental and physical health symptoms (Elgar et al, 2015). Other research on children and youth found that national or regional income inequality relates to poor self-rated health (Rözer & Volker, 2016) (Eckenrode, Smith, McCarthy, & Dineen, 2014). Pickett and Wilkinson (2007; reported that international differences in UNICEF indices of child well-being relate more closely to national income inequality than to country wealth.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of adolescent health in 34 mostly high-income countries found that national income inequality related to higher body mass indices, less physical activity, and more self-rated mental and physical health symptoms (Elgar et al, 2015). Other research on children and youth found that national or regional income inequality relates to poor self-rated health (Rözer & Volker, 2016) (Eckenrode, Smith, McCarthy, & Dineen, 2014). Pickett and Wilkinson (2007; reported that international differences in UNICEF indices of child well-being relate more closely to national income inequality than to country wealth.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Unfortunately, very little is currently known about how income inequality affects prenatal development, parent-child attachment, early temperament, and parenting styles in various cultural contexts. Some research in US has found that state-level income inequality correlates to preterm births, low birth weight, and infant mortality (Olson, Diekema, Elliot, & Renier, 2010) and to rates of child maltreatment (Eckenrode et al, 2014). Still, international replication and extension of these studies are needed to determine the total impact of income inequality on infant and child development and to devise early interventions that might mitigate these influences in early life.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…ACEs were surprisingly common in the original CDC sample, but are even more pervasive in poor, minority, marginalized, and oppressed populations commonly served by social workers (Eckenrode, Smith, McCarthy, & Dineen, 2014;Larkin, Felitti, & Anda, 2014). Pathogenic parenting and deprivational environments hinder family functioning and reinforce maladaptive coping styles, and household dysfunction is often exacerbated by the stress of impoverished socioeconomic conditions (Patterson, DeBaryshe, & Ramsey, 1990).…”
Section: The Frequency and Correlates Of Aces In Criminal Populationsmentioning
confidence: 99%
“…Recent survey data confirm that both poverty and income inequality are positively associated with the rates of protective service referrals for child maltreatment. 88 Within families, poverty is associated with intimate partner violence, maternal depression, single-parent families, and parental substance abuse, all of which are risk factors for child maltreatment. 89 102 For example, poverty is a risk factor for lead exposure in the home, and poor black children are twice as likely as poor Hispanic and white children to have concentrations of lead in their blood of at least 2.5 μg/dL (33% vs 17% and 13%, respectively).…”
Section: Unintentional Injuries and Child Maltreatmentmentioning
confidence: 99%